PENGARUH TATA TERTIB KERJA, PENGAWASAN MANAJERIAL DAN DISIPLIN TERHADAP SEMANGAT KERJA PEGAWAI - ANWAR IBRAHIM (STIE Indonesia Malang, 2016)
This study intended to analyze the influence of work rules, managerial supervision and selfdisciplineon morale Staff Secretariat of the Council of Representatives of Regional Dompu.Using multiple linear regression analysis using SPSS software, this study analyzed a sampleof 27 Staff Secretariat of the Council of Representatives of Regional Dompu. The results ofthis study states that work rules significant effect on employee morale. Managerial oversightsignificant effect on employee morale. Personal discipline significant effect on morale StaffSecretariat of the Council of Representatives of Regional Dompu Dompu. Another result ofthis analysis states that managerial oversight dominant influence on morale Staff Secretariatof the Council of Representatives of Regional Dompu.Keywords: Rules of work, managerial oversight, discipline and morale